2021
DOI: 10.25046/aj060442
|View full text |Cite
|
Sign up to set email alerts
|

Automated Agriculture Commodity Price Prediction System with Machine Learning Techniques

Abstract: The intention of this research is to study and design an automated agriculture commodity price prediction system with novel machine learning techniques. Due to the increasing large amounts historical data of agricultural commodity prices and the need of performing accurate prediction of price fluctuations, the solution has largely shifted from statistical methods to machine learning area. However, the selection of proper machine learning techniques for automated agriculture commodity price prediction still has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In comparison to stacked models and multiple regression, model performance is lower at predicting values, as seen by higher MAPE values approximately 11% observed of SVR for 15 days of average prediction. Most of the researchers have focused LSTM (long short-term memory) (2,4) , Neural network (20) , which needs a huge amount of data as compared to the meta-model presented in the current study, and Traditional statistical approaches like ARIMA, SARIMAX (3,5,11) , which required high computing capacity of classical Machine learning models such as autoregressive models, Feature engineering is performed manually and not able to learn more complex data patterns ultimately. Almost all the published research work reported improvement in accuracy with Bi -Direction LSTM.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison to stacked models and multiple regression, model performance is lower at predicting values, as seen by higher MAPE values approximately 11% observed of SVR for 15 days of average prediction. Most of the researchers have focused LSTM (long short-term memory) (2,4) , Neural network (20) , which needs a huge amount of data as compared to the meta-model presented in the current study, and Traditional statistical approaches like ARIMA, SARIMAX (3,5,11) , which required high computing capacity of classical Machine learning models such as autoregressive models, Feature engineering is performed manually and not able to learn more complex data patterns ultimately. Almost all the published research work reported improvement in accuracy with Bi -Direction LSTM.…”
Section: Resultsmentioning
confidence: 99%
“…An increase in differential order will take more time to run models like ARIMA, SARIMAX. (2)(3)(4)(5)11,20) and Logarithmic Complexity increases with the SARIMAX, Same doesn't apply to LSTM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They used climate and soil properties to predict crop production or weather-related events such as rainfall [43,44,101,[114][115][116]. Studies have also focused on financial objectives using only econometric historical observations [99,[117][118][119]. Our work pioneers this approach by combining weather, biophysical, and economic data into an aggregate forecasting framework which is an under-researched area [99].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, an accurate forecast model is crucial for both the investor community and the investment choices of mining businesses. Previous writers have underlined [29] that it is crucial for commodities markets and the global economy to precisely estimate diamond price fluctuations. The price fluctuations of diamonds have been modeled using traditional mathematical and statistical time series prediction techniques.…”
Section: Iiliterature Reviewmentioning
confidence: 99%